The PGPR Bacillus aryabhattai promotes soybean growth via nutrient and chlorophyll maintenance and the production of butanoic acid - Mun, Bong-Gyu; Hussain, Adil; Park, Yeon-Gyeong; Kang, Sang-Mo; Lee, In-Jung; Yun, Byung-Wook (Frontiers in Plant Science, 2024)
Plant growth-promoting rhizobacteria (PGPR) colonize plant roots, establish a mutualistic relationship with the plants and help them grow better. This study reports novel findings on the plant growth-promoting effects of the PGPR Bacillus aryabhattai. Soil was collected from a soybean field, PGPR were isolated, identified, and characterized for their ability to promote plant growth and development. The bacterium was isolated from the soybean rhizosphere and identified as B. aryabhattai strain SRB02 via 16s rRNA sequencing. As shown by SEM, the bacterium successfully colonized rice and soybean roots within 2 days and significantly promoted the growth of the GA-deficient rice cultivar Waito-C within 10 days, as well as the growth of soybean plants with at least six times longer shoots, roots, higher chlorophyll content, fresh, and dry weight after 10 days of inoculation. ICP analysis showed up to a 100% increase in the quantity of 18 different amino acids in the SRB02-treated soybean plants. Furthermore, the 2-DE gel assay indicated the presence of several differentially expressed proteins in soybean leaves after 24 hrs of SRB02 application. MALDI-TOF-MS identified β-conglycinin and glycinin along with several other proteins that were traced back to their respective genes. Analysis of bacterial culture filtrates via GCMS recorded significantly higher quantities of butanoic acid which was approximately 42% of all the metabolites found in the filtrates. The application of 100 ppm butanoic acid had significantly positive effects on plant growth via chlorophyll maintenance. These results establish the suitability of B. aryabhattai as a promising PGPR for field application in various crops